The development of the asylum law and refugee protection regimes in Portugal, 1975–2017 - Sousa, Lúcio (2018)
This article examines the development of the legislation on asylum law and refugee policies in Portugal. The assessment begins in 1975, the year when democracy was re-established in the country, following the 1974 Carnation Revolution, and ends in 2015, the year the European asylum crisis started. We want to discuss whether, during this period, the policies established indicate an open regime, with an inte- grationist perspective, or whether they proclaim a closed regime with an exclusivist position; in other words, whether the asylum system promoted an active policy of receiving and integrating refugees, or whether the policies pursued intended to limit the access of refugees to the borders of the state. In order to understand these developments, we ana- lyze asylum application figures and asylum laws, trying to understand the main circumstantial contexts that influence them, namely Portugal’s integration in the European Union.